Conventional vs. Universal Entry Point: A Postoperative Radiological comparison of Freehand Thoracic Pedicle Screw Placement (Bangladesh Journal of Neurosurgery, 2026)
Objective: To observe the difference of postoperative CT scan findings between using conventional and universal entry point for pedicle screw placement among the study subjects in all levels of the thoracic spine. Methods: This interventional study was conducted in the Neurosurgery Department of Dhaka Medical College Hospital. A total of 43 samples were taken. 31 Patients were categorized as Group-A (universal entry point) and 12 patients as group-B (conventional entry point). Patients who had presented with compressive dorsal myelopathy due to either traumatic thoracic fractures or kyphotic deformity, Pott’s disease or patients having neoplastic bony lesions requiring fixation were enrolled in this study. All patients underwent Magnetic Resonance Imaging for establishing diagnosis. CT scan of thoracic spine was done postoperatively within 1 week in all cases and pedicle violations were measured by Surgimap (version 2.3.2.1) software. Data was collected and compiled. Results: Mean age of the patients was 44.9 ± 11.4 years. A total of 224 screws were inserted in both groups in different thoracic levels. Maximum screws were inserted in T10, T11 and T12 thoracic levels. Pedicle wall violation in universal entry point group was 17.1% and in conventional group it was 27.3%. 82.9% screws were fully contained within the pedicle wall in universal group and in conventional group it was 72.7%. Per-operative unintended durotomy was observed in 2 (6.5%) cases, screw in the fractured pedicle in 3 (9.7%) cases, CSF leak in 1 (3.2%) case, pulmonary complication in 1 (3.2%) case, nerve root irritation in 3 (9.7%) cases and no incidence of major vascular injury occurred in group-A. In Group-B, unintended durotomy was observed in 1 (8.3%) case and screw in the fractured pedicle in 1 (8.3%) case. Conclusion: This study shows that there was no significant difference of pedicle wall violation and in post-operative CT scan between using the universal and the conventional entry points. Per-operative complications were also similar in both groups.Bang. J Neurosurgery 2025; 14(2): 77-84